Novel positive allosteric modulator of protease‐activated receptor 1 promotes skin wound healing in hairless mice - Seo, Yohan; Heo, Yunkyung; Jo, Sungwoo; Park, So‐Hyeon; Lee, Chulho; Chang, Jiwon; Jeon, Dong‐Kyu; Kim, Tae Gun; Han, Gyoonhee; Namkung, Wan (British journal of pharmacology, 2021)
Background and Purpose Protease‐activated receptor 1 (PAR1) is a GPCR expressed in several skin cell types, including keratinocyte and dermal fibroblast. PAR1 activation plays a crucial role in the process of skin wound healing such as thrombosis, inflammation, proliferation and tissue repair. In the present study, we identified a novel positive allosteric modulator of PAR1, GB83, and investigated its effect on skin wound healing. Experimental Approach The enhancement of PAR1 activity by GB83 was measured using Fluo‐4 calcium assay. In silico docking analysis of GB83 in PAR1 was performed using dock ligands method (CDOCKER) with CHARMm force field. Effects of GB83 on cell viability and gene expression were observed using MTS assay and quantitative real‐time PCRs, respectively. SKH‐1 hairless mice were used to investigate the wound healing effect of GB83. Key Results We demonstrated that GB83 did not activate PAR1 by itself but strongly enhanced PAR1 activation by thrombin and PAR1‐activating peptide (AP). In silico docking analysis revealed that GB83 can bind to the PAR1 binding site of vorapaxar. GB83 significantly promoted PAR1‐mediated cell viability and migration. In addition, the enhancement of PAR1 activity by GB83 strongly increased gene expression of TGF‐β, fibronectin and type I collagen in vitro and promoted skin wound healing in vivo. Conclusion and Implications Our results revealed that GB83 is the first positive allosteric modulator of PAR1 and it can be a useful pharmacological tool for studying PAR1 and a potential therapeutic agent for skin wound healing.